The Role of Trade and Offshoring in the Determination of Relative Wages and Child Labour - Alessandro Cigno; Giorgia Giovannetti; Laura Sabani (Center for Economic Studies and ifo Institute (CESifo), 2017)
Incorporating family decisions in a two-period.model of the world economy, we predict that trade liberalization raises the skill premium and reduces child labour in developing countries where the adult labour force is sufficiently well educated to attract production activities from abroad that will increase the demand for skilled relative to unskilled labour. Elsewhere, liberalization will reduce the skill premium, but it will not necessarily raise child labour. Our prediction is not rejected by the data, and it explains why child labour is negatively associated with trade openness in those developing countries where the labour force was relatively well educated when the liberalization took place, but not in the others.
Keywords: D13; D33; F16; J13; J24; 330; child labour; education; trade liberalization; skill endowments; skill premium